An alternative approach to designing hydrogeological conceptual models in cases of scarce field data - Teramoto, Elias Hideo [UNESP]; Montanheiro, Filipe [UNESP]; Chang, Hung Kiang [UNESP] (Elsevier, 2021)
The sensitivity of the derivative analysis to the variation of flow rates allows it to solve ambiguities, provide diagnostics of the flow dimension, and identify the boundary conditions of the tested aquifer. Based on the results of a derivative analysis, it was hypothesized that the set of assumptions for the fitted solution to the drawdown curve are valid for the tested aquifer. Thus, combining the derivative analysis results and the detailed geological characterization, a new approach was developed to build preliminary conceptual hydrogeological models in cases where field data are scarce. Applying this approach, it was concluded that basaltic aquifers in the Serra Geral Aquifer System (SGAS) are comprised of leaky confined aquifers, which the alternation of basalt floods that have permeable horizons at the top and with low permeability of interior flow. The simulated drawdown curve in a transient flow model perfectly matched with the drawdown curve recorded in the field, thus supporting the suitability of the built conceptual model. This statement challenges the prevailing theory that conceptualizes SGAS as a fractured aquifer. Conclusively, the current approach is capable of producing suitable conceptual models in cases of field data scarcity. Future investigations in other complex geological contexts may validate the present approach.
Keywords: Aquifer test; Diagnostic plot; Groundwater flow model; Serra geral aquifer